Effect of Sintering Temperature on the Microstructure Behavior of Gelcasted Porous Ceramics Using Cassava Starch as Pore Template - Suriati Eka Putri; Diana Eka Pratiwi; Rachmat Triandi Tjahjanto; Nita Magfirah Ilyas; Dahlang Tahir; Abd Rahman; Heryanto Heryanto (Universitas Gadjah Mada, 2023)
The gelcasting technique was employed to fabricate porous ceramics utilizing kaolinite clay as the base material with a combination of 20 wt.% cassava starch. The utilization of cassava starch as a pore-template material is a sustainable and eco-friendly approach. The dry mixture compacted pellets underwent calcination for 2 h at three distinct sintering temperatures, namely 900, 1000, and 1100 °C. The present study investigated the impact of sintering temperatures on various ceramic properties, including but not limited to porosity, hardness, crystallinity, lattice strain, and morphology. Furthermore, an increase in sintering temperature led to a reduction in crystallinity of the ceramic material from 81.71 to 78.06%, while the lattice strain increased, as determined by the full width at half maximum peak diffraction calculation. The study determined that the pore size remained microporous (21 Å) across all temperature treatments. Ultimately, a porous ceramic material was fabricated, exhibiting a porosity of 39.44% by volume and a desirable hardness of 94 HB. The optimal sintering temperature for this material was found to be 900 °C. The anticipated application of the porous ceramic, which has taken on a pellet shape, is as a catalyst support for wastewater filtration in the future.